PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PERTAMBANGAN BATUBARA ILEGAL: STUDI KASUS DI KABUPATEN HULU SUNGAI SELATAN, KALIMANTAN SELATAN - Polsiapri Lumban Gaol; Muhammad Faizal Anshari; Dani Anugrah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research examines law enforcement against illegal coal mining crimes in Hulu Sungai Selatan Regency, South Kalimantan. Using normative legal research method, this research analyzes the application of criminal sanctions based on the Mining Law and Environmental Law, as well as community participation in monitoring illegal mining. The results show that law enforcement is carried out through two main legal instruments: Minerba Law, which provides criminal sanctions of up to 10 years' imprisonment and fines of up to 10 billion rupiah, and PPLH Law, which provides varied sanctions based on the level of intent and the impact of environmental damage. Community participation in monitoring faces various obstacles, including limited human resources, monitoring budgets, and coordination between law enforcement agencies, as well as the risk of intimidation of whistleblowers. A comprehensive approach involving cooperation between the government, communities and other stakeholders is needed to create a more effective law enforcement system.